Pendampingan Manajemen Pakan Sapi Bagi Kelompok Peternak dan Petani Pengelola Hutan Kemasyarakatan di Desa Paopao Kabupaten Barru, Provinsi Sulawesi Selatan - Akhsan, Fitriana; Bando, Nurjannah; Thamrin, Syahruni; Kadir, Muhammad; Nurbaeti, Nurbaeti (Penerbit Widina, Widina Media Utama, 2024)
The existence and sustainability of the beef cattle business introduced to members of the Community Forest Management Farmer Community in Paopao Village, faces the problem of feed availability, while during the dry season is a challenge where natural feed is difficult to obtain.The farmers must be able to organize feeding, formulate and record healthy feeding for livestock. Animal feed management training activities aim to equip farmers and breeders with the ability to provide, organize and produce healthy feed for livestock using a variety of easily obtained ingredients, especially formulations from potential feed plants Indigofera sp and no longer depend on natural feed in the form of plants and pure forage. Service activities are carried out through counseling and discussion, training / practice of making complete feed formulations and assistance. The results of training and mentoring activities showed an increase in the ability to manage Indigofera sp. feed plants, and the ability to formulate complete feed for cattle, and management of feeding it to livestock. The success of this program is supported by the active participation of partners both in counseling, FGDs and training and mentoring processes carried out.ABSTRAKKeberadaan dan keberlangsungan usaha ternak sapi yang dilakukan pada anggota masyarakat petani pengelola hutan kemasyarakatan di Desa Paopao, sering menghadapi masalah ketersediaan pakan, sementara pada musim kemarau pakan alami sulit didapatkan. Para peternak harus mampu mengatur pemberian pakan, memformulasi dan melakukan recording pemberian pakan sehat untuk ternak. Kegiatan pelatihan manajemen pakan ternak bertujuan membekali petani dan peternak kemampuan menyediakan, mengatur dan memproduksi pakan sehat bagi ternak dengan menggunakan berbagai bahan yang mudah diperoleh, utamanya formulasi dari tanaman pakan potensial Indigofera sp dan tidak lagi tergantung pada pakan alami berupa tanaman dan hijauan murni. Kegiatan pengabdian dilakukan melalui penyuluhan dan diskusi, pelatihan / praktek pembuatan formulasi pakan komplit dan Pendampingan. Hasil kegiatan pelatihan dan pendampingan menunjukkan peningkatan kemampuan dalam pengelolaan tanaman pakan Indigofera sp, dan kemampuan formulasi pakan komplit untuk ternak sapi, dan manajemen pemberiannya pada ternak. Keberhasilan program ini didukung oleh partisipasi aktif mitra baik dalam penyuluhan, FGD dan pelatihan serta pendampingan proses yang dilakukan.